Translating flouting maxim in the narrative dialogue of Resident Evil 4 Remake - I Kadek Ade Klaus Nurjana Putra; Hikmaharyanti, Putu Desi Anggerina (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study investigates the flouting of conversational maxims in the English dialogue of Resident Evil 4 Remake and examines how the implied meanings are translated into Indonesian using AI Copilot. The research adopts a qualitative descriptive design to identify the types of flouted maxims Quantity, Quality, Relevance, and Manner and to analyse how their pragmatic functions are preserved, shifted, or lost in the translation process. A total of six dialogue samples from Chapters 1 to 4 were selected and analysed based on Grice’s Cooperative Principle and modified translation procedures derived from Vinay and Darbelnet’s theoretical framework. Each dialogue was examined in its narrative context, focusing on the pragmatic implicature and the translation strategy used. The results reveal that flouted maxims serve various narrative functions in the source language, such as sarcasm, emotional suppression, and character expression. However, when translated literally by AI Copilot, many utterances experienced pragmatic distortion or loss of implicature, particularly in emotionally charged or sarcastic lines. Some translations using modulation or adaptation were more successful in preserving tone and intent. The study highlights the limitations of machine translation in preserving pragmatic nuance and emphasizes the need for human revision, especially in genre-sensitive content such as horror games. This research contributes to the fields of pragmatics, translation studies, and game narrative by illustrating the complex relationship between language, meaning, and digital storytelling.